Pengembangan Media Komik Digital untuk Literasi Sains pada Pembelajaran IPAS Kelas 5 di MI Al-Washliyah Perbutulan - Oca Sakilah; Atikah Syamsi; Nur Atikoh (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study intends to create digital comic resources to enhance scientific understanding among fifth-grade learners at MI Al-Washliyah Perbutulan. The motivation behind this research stems from students' enthusiasm for science literacy and the insufficient availability of varied media, particularly digital options. The methodology followed is Research and Development (RandD) using the ADDIE development framework, which includes five phases: Analysis, Design, Development, Implementation, and Evaluation. Data collection tools include validation surveys from experts, student feedback, and assessments of science literacy through pretests and posttests. Findings indicated that the digital comic resources produced were deemed valid with ratings of 97% from media specialists, 97% from subject matter specialists, and 75% from language experts. The comics’ practicality was rated at 88%, classified as practical for educational purposes, and they proved effective in enhancing students' scientific literacy, demonstrated by a 0. 66 increase in the N-Gain score, which is considered quite effective. These materials were created using digital platforms like Pixton and Canva, making them easily accessible and engaging for students. Therefore, digital comics are appropriate as a technology-driven educational resource to boost scientific literacy in elementary education.